Cepstral and Perceptual Investigations in Female Teachers With Functionally Healthy Voice - Phadke, Ketaki Vasant; Laukkanen, Anne-Maria; Ilomäki, Irma; Kankare, Elina; Geneid, Ahmed; Švec, Jan G (Journal of voice, 2020)
PURPOSE: The present study aimed at measuring the smoothed and non-smoothed cepstral peak prominence (CPPS and CPP) in teachers who considered themselves to have normal voice but some of them had laryngeal pathology. The changes of CPP, CPPS, sound pressure level (SPL) and perceptual ratings with different voice tasks were investigated and the influence of vocal pathology on these measures was studied. METHOD: Eighty-four Finnish female primary school teachers volunteered as participants. Laryngoscopically, 52.4% of these had laryngeal changes (39.3% mild, 13.1% disordered). Sound recordings were made for phonations of comfortable sustained vowel, comfortable speech, and speech produced at increased loudness level as used during teaching. CPP, CPPS and SPL values were extracted using Praat software for all three voice samples. Sound samples were also perceptually evaluated by five voice experts for overall voice quality (10 point scale from poor to excellent) and vocal firmness (10 point scale from breathy to pressed, with normal in the middle). RESULTS: The CPP, CPPS and SPL values were significantly higher for vowels than for comfortable speech and for loud speech compared to comfortable speech (P < 0.001). Significant correlations were found between SPL and cepstral measures. The loud speech was perceived to be firmer and have a better voice quality than comfortable speech. No significant relationships of the laryngeal pathology status with cepstral values, perceptual ratings, or voice SPLs were found (P > 0.05). CONCLUSION: Neither the acoustic measures (CPP, CPPS, and SPL) nor the perceptual evaluations could clearly distinguish teachers with laryngeal changes from laryngeally healthy teachers. Considering no vocal complaints of the subjects, the data could be considered representative of teachers with functionally healthy voice.
Keywords: dospělí; Teachers’ voice; Female; Laryngeal pathologies; akustika; měření tvorby řeči; Adult; ženské pohlaví; CPPS; Occupational Health; Predictive Value of Tests; Finland; prediktivní hodnota testů; lidé; larynx; laryngoskopie; Speech Acoustics; učitelé; Humans; nemoci z povolání; Acoustics; Speech Production Measurement; CPP; Larynx; poruchy hlasu; Voice SPL; Occupational Diseases; akustika řeči; lidé středního věku; Voice Disorders; hygiena práce; Voice Quality; School Teachers; kvalita hlasu; Middle Aged; Laryngoscopy; Perceptual evaluation; Finsko